Legal Analysis of Reappointing Land Deed Officials (PPAT) After Imprisonment for Minor Crimes - Parama Artha, Krisna Adi; Noerdajasakti, Setiawan (The Islamic Education and Multiculturalism Foundation, 2024)
Land Deed Officials (PPATs) have an important role in ensuring the legality of land transactions, which demands high standards of integrity and public trust. However, Article 10 paragraphs (3) and (4) of Government Regulation Number 24 Year 2016 only regulates sanctions for PPATs who are sentenced to five years or more, while there is no clear regulation regarding sanctions for PPATs who are sentenced to minor criminal penalties under five years. This creates a legal vacuum that has the potential to undermine public confidence in the PPAT profession and the land law system in Indonesia. This study aims to analyze the feasibility of PPATs who are sentenced to minor criminal penalties to return to office, as well as recommend revisions to regulations to fill the legal vacuum. The research method used is normative juridical with a statutory and conceptual approach, and uses primary and secondary legal materials. The results show that PPATs who have criminal records, even if they are minor, find it difficult to regain public trust and potentially tarnish the integrity of the profession. Therefore, a revision of regulations is needed to establish strict sanctions and maintain morality standards and public trust in the PPAT profession.